Perbandingan Keterampilan Berpikir Kritis dan Hasil Belajar Biologi Siswa Ditinjau Dari Tipe Kepribadian Ekstrovert dan Introvert di SMA Negeri Kota Makassar - Hastin Indrawati; Firdaus Daud; Alimuddin (Jurnal Biotek, 2022)
Education is a long term investment of human resources which has strategic values for the continuity of human civilization in the world. The teaching and learning process is a core of the overall learning process. The critical thingking skills is one of the main problems in learning because the domination of teachers who given less access for students to develop independently through their own findings and thingking process. The low learning outcomes also becomes a complex problem to date because the learning process is still center on the teacher; thus, students become passive. Teachers prefer to apply lecture method because it does not need tools and practice materials and only explain the concept continued in the textbook. The students are not being given the method which centered on the students. The study aims at examining (i) the critical thingking skills of students who have extrovert and introvert personalities at SMAN (public senior high schools) in Makassar city, (ii) the Biology learning outcomes of students who have extrovert and introvert personalities at SMAN in Makassar city, (iii) the difference of critical thingking skills between extrovert personality students and introvert personality students at SMAN in Makassar city, and (iv) the difference of biology learning outcomes between extrovert personality students and introvert personality students at SMAN in Makassar city. The study was ex-post facto. Data were collected by employing personality questionnaire, critical thingking skill test, and documentation of learning outcomes scores. The results of the study reveal that (i) the critical thingking skills of extrovert personality students are in well delevop category and the introvert personality students are in well develop category as well, (ii) the Biology learning outcomes of extrovert personality students are in high category and the introvert personality students are in high category as well, (iii) there is a difference of critical thingking skills between extrovert personality students and introvert personality students, and (iv) there is no difference of Biology learning outcomes between extrovert personality students and introvert personality students. Keywords: Critical Thingking Skills, Biology Learning Outcomes, Extrovert Personality and Introvert Personality